Outcomes of Ureteral Stent Placement for Hydronephrosis in Patients with Gynecological Malignancies - Kurata, Saya (Curr Urol, 2017)
OBJECTIVE: We examined the outcomes of patients undergoing ureteral stent placement for hydronephrosis that occurred during treatment for gynecological malignancies. MATERIALS AND METHODS: From January 2004 to December 2009, we enrolled 33 patients with 45 ureters undergoing ureteral stent placement for hydronephrosis which occurred during treatment for gynecological malignancies. We examined the outcomes of the patients after stent placement. RESULTS: The causes of hydronephrosis were obstruction of the urinary tract by a tumor (n = 22), obstruction due to lymph node swelling (n = 6), ureteral stenosis after radiation therapy (n = 4), and others (n = 1). The ureteral stent was inserted into both ureters in 12 cases, and into one ureter in 21 cases. Ureteral stents were replaced 1–26 times during the observation period (median 3 times). Eighteen (40%) ureteral stents were removed. The reasons for ureteral stent removal were hydronephrosis improvement (11 ureters, 24.4%), a change to nephrostomy (cystectomy: 1 ureter, progression of ureteral stenosis: 2 ureters), renal atrophy (3 ureters), and ureteral dilatation (1 ureter). All of the cases in which ureteral stent withdrawal due to hydronephrosis improvement were cases in which the ureter was compressed by a tumor and were lower ureteral obstructions. Twenty-one patients (64%) died due to cancer after stent placement. The periods from the first stent placement to death ranged from 1 to 58 months (median 18 months). CONCLUSION: Ureteral stent placement was associated with a poor prognosis in patients with gynecological malignancies. There were a few cases in which stent withdrawal became possible due to the improvement of hydronephrosis. In such cases, the withdrawal rate varied according to the cause and obstructive level.